Liver perfusion scintigraphy prior to and after transjugular intrahepatic portosystemic shunts (TIPS) in patients with portal hypertension - Willkomm, P.; Schoniburg, A.; Brensing, K. A.; Reichmann, K.; Bangard, M.; Overbeck, B.; Sauerbruch, T.; Biersack, H. J. (Nuklearmedizin - NuclearMedicine, 2000)
Purpose: This investigation was performed to compare the hemodynamic results of the transjugular intrahepatic portosystemic shunt, a new interventional treatment for portal hypertension, with those observed after the established surgical shunt interventions. Methods: We examined 22 patients with portal hypertension due to liver cirrhosis before and after elective TIPS by liver perfusion scintigraphy. The relative portal perfusion was determined before and after the shunt procedure. Additionally, we measured the portal pressure gradient (PPG: portal-central venous pressure, mmHg). Results: Prior to TIPS, the relative portal perfusion was significantly reduced to 22 ± 9.1%. After the intervention we calculated values of 23.1 ± 10,7% in the TIPS-group (p = 0.67; not significant). In spite of unchanged portal perfusion, the portal pressure was significantly (p <0.001) reduced from 25.6 ± 5.3 to 14.8 ± 4 mm Hg. Conclusion: These results suggest that the reduction of portal hypertension by TIPS is effective. The portal perfusion is maintained by TIPS suggesting that liver perfusion is preserved to a higher degree.
Keywords: Liver perfusion scintigraphy; portal hypertension; transjugular intrahepatic portosystemic shunt